2005
DOI: 10.1001/jama.293.18.2238
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Phonocardiographic Third and Fourth Heart Sounds and Objective Measures of Left Ventricular Function

Abstract: ContextThe third (S 3 ) and fourth (S 4 ) heart sounds detected by phonocardiography are considered to represent the criterion standards of the gallop sounds, but their test characteristics have not been explored.Objective To determine the diagnostic test characteristics of the S 3 and S 4 for prediction of left ventricular dysfunction using a computerized heart sound detection algorithm.Design, Setting, and Participants Prospective study of 90 adult patients undergoing elective left-sided heart catheterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(66 citation statements)
references
References 24 publications
3
61
0
2
Order By: Relevance
“…17 We have previously shown that the S 3 is associated with objective measures of cardiac dysfunction, including reduced ejection fraction, elevated left ventricular filling pressure, and elevated BNP. 18,19 Similarly, an audible S 4 portends an adverse prognosis after acute myocardial infarction. 20 However, the ability of medical students and physicians to detect these valuable auscultatory signs has been poor.…”
Section: Discussionmentioning
confidence: 99%
“…17 We have previously shown that the S 3 is associated with objective measures of cardiac dysfunction, including reduced ejection fraction, elevated left ventricular filling pressure, and elevated BNP. 18,19 Similarly, an audible S 4 portends an adverse prognosis after acute myocardial infarction. 20 However, the ability of medical students and physicians to detect these valuable auscultatory signs has been poor.…”
Section: Discussionmentioning
confidence: 99%
“…With the great majority of AHF patients actually being chronic heart failure patients (and thereby known to the local health care system) and with physical signs that are easily identifiable even by junior physicians, it may come as a surprise to often hear that accuracy of HF diagnosis overall is quite poor [20,21]. In one study, the combination of clinical signs had only a 58% rate of sensitivity in detecting patients with elevated pulmonary capillary wedge pressure (PCWP) [22], whereas radiographic pulmonary congestion was absent in 53% of patients with a PCWP of 16 to 29 mmHg and in 39% of patients with a PCWP of 30 mmHg [23].…”
Section: Diagnostic Challengesmentioning
confidence: 99%
“…The ability of the acoustic cardiography system to amplify the recorded sounds and determine their frequencies makes S4 detection more reliable than it is with auscultation. Also, acoustic cardiography provides an automated interpretation of the diagnostic findings so that a high level of skill in either heart sound detection or ECG interpretation is not required [29] . The findings of the present pilot study showed that, at similar diagnostic specificities, the sensitivities of the exercise-related S4 exceeded those of exercise-related ST segment depression for detecting CAD.…”
Section: B Amentioning
confidence: 99%